Pelatihan Sertifikasi Halal dalam Upaya Peningkatan Kepuasan Pelanggan Sebagai Bagian dari Scale-Up Business Bagi UMKM - Rachma Rizqina Mardhotillah; Endah Budi Permana Putri; Denis Fidita Karya; Riyan Sisiawan Putra; Hidayatul Khusnah; Mohamad Rijal Iskandar Zhulqurnain; Pance Mariati (Jurnal Surya Masyarakat, 2022)
MSME actors have limited knowledge in applying for halal certification so that it becomes an obstacle in implementing halal product guarantees in Indonesia. Whereas the halal logo on the packaging has an impact on purchasing decisions and consumer satisfaction. Community service aims to provide training on the importance of halal certification as an effort to increase customer satisfaction for MSME actors. The target of the activity is 26 MSMEs in Surabaya. The method used is lectures and questions and answers followed by distributing knowledge questionnaires about halal certification and consumer satisfaction as material for evaluating activities. Furthermore, the data were analyzed using the Paired Sample Test. The results of the analysis showed that there was a significant increase in knowledge (p-value 0.000). This is indicated by the average knowledge score before training from 3.81 to 6.50 after being given training. Furthermore, MSME actors expect there are activities to assist in the registration of halal certification.